A Review on Phytosomes for Effective Topical Drug Delivery - Ajay Prakash Nemade; Dr. Sandeep C. Atram; Dr. Vikrant P. Wankhade; Nishan N. Bobade; Dr. Shrikant D. Pande (Asian Journal of Pharmaceutical Research and Development, 2026)
In recent years, there has been growing interest in the therapeutic potential of medicinal herbs and the bioactive compounds they contain for treating various health conditions. However, challenges such as poor bioavailability and limited targeting ability may reduce their effectiveness in clinical applications. As a result, enhancing the bioavailability of these compounds has become a critical focus to maximize their therapeutic impact. Phytosome-based nanotechnology offers a promising solution, especially for improving the topical delivery of herbal bioactives. Phytosomes, which are lipid-based nanoparticles, significantly enhance the absorption and penetration of phytochemicals across biological barriers, such as the skin. This review examines how encapsulating phytochemicals in a phytosome—a complex of plant compounds and phospholipids—can enhance their absorption, bioavailability, and ability to penetrate the skin.